Evaluating cognitive rehabilitation in multiple sclerosis: on the bumpy road to establishing evidence - das Nair, Roshan (Future Medicine, 2015)
There is marked enfeeblement of the memory; conceptions are formed slowly; the intellectual and emotional faculties are blunted in their totality,” Charcot (1877) reportedly noted about people with multiple sclerosis (MS) [1]. Despite these early observations of what we now refer to as ‘cognitive deficits’ and ‘mood disorders’, the magnitude and severity of these problems in MS were not considered seriously until over 100 years later. By the early 1990s, studies had begun to consistently demonstrate that people with MS reported cognitive problems.